Are Men Benefiting from the New Economy : Male Economic Marginalization in Argentina, Brazil, and Costa Rica - Arias, Omar (World Bank, Washington, DC, 2014)
The economies of Latin America have undergone extensive reforms, raising concerns about how these changes have affected the labor market. But there is also increasing concern that the reforms may have deeper social ramifications as the new economies strain the ability of certain groups of men to work and to earn good wages, fulfilling their traditional role as providers. Using household surveys broadly covering the period 1988-97 in urban areas of Argentina, Brazil, and Costa Rica, Arias examines the patterns of unemployment and real wage growth for distinct groups of male workers to see whether there is evidence of a deterioration in men's ability to be economically self-sufficient. He finds no general trend of male economic marginalization. The incidence and duration of unemployment have increased the most for the typically vulnerable group-young, less educated, informal sector workers-but the increased duration of unemployment has also affected older and more educated men. With respect to wages, density and quantile regression analysis indicates that the usual stories of wage marginalization of vulnerable workers can hardly explain the observed variety of wage growth patterns in the three countries. The positive wage performance has been concentrated mainly in the higher quantiles of the conditional wage distribution. This suggests that differences in unobservable worker characteristics, such as industriousness, labor market connections, and quality of schooling, have been key determinants of the ability of male workers in the region to adapt to economic restructuring. These results suggest that assistance should be targeted to some groups so that frustrations in asserting an economic identity do not lead to aggressive behavior. But they also show that we must look elsewhere for the roots of the increase in socially dysfunctional behavior.